Anaesthesiology & critical care postgraduate training in Malaysia: guide for applicants version 1, 2023 - Md Hashim, Noorjahan Haneem; Md Ralib, Azrina; Chan, Yoo Kuen; Foo, Li Lian; Shariffuddin, Ina Ismiarti; Md Zain, Jaafar; Abdul Mukmin, Laila; Lee, Choon Yee; Mansor, Marzida; Zakariah, Mohd Fahmi; Nik Mohamad, Nik Abdullah; Ibrahim, Noor Airini; et al. (Majlis Dekan Fakulti Perubatan Universiti Awam Malaysia, UM, 2023)
This document is a guide for potential candidates applying to enter Postgraduate training in Anaesthesiology and Critical Care. It provides information on the entry requirements and process for the specialty training programme, the selection process, and what the training entails. It is an extract from the National Postgraduate Curriculum for Anaesthesiology and Critical Care, and provides key summaries about the training, structure, syllabus and assessments.